Effectiveness Of Accounting Information System In Cash Billing And Receipts At Perumda Drinking Air Tirta Perwitasari In 2023 (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the effectiveness of implementing the Accounting Information System (AIS) in billing and cash receipt processes at Perumda Air Minum Tirta Perwitasari Purworejo. The research employs a qualitative descriptive approach using primary data from interviews and observations, and secondary data from financial reports and company documents. The results indicate that the AIS has been highly effective, with a billing effectiveness ratio of 98.19% in 2023, slightly decreasing from 99.73% in 2022 due to tariff adjustments. The system also contributed to a 9.28% increase in water sales revenue in 2024, strengthened internal controls, and improved the accuracy and timeliness of financial reporting. Although minor technical issues such as network disruptions and delayed data synchronization remain, they do not significantly affect the overall system effectiveness
Keywords: Accounting Information System; Effectiveness; Billing; Cash Receipts; Regional Water Company